Antibacterial Potential of Aloe vera against Staphylococcus aureus and Streptococcus agalactiae isolated from Mastitic Milk: Antibacterial Potential of Aloe vera - Arain, Muhammad Bilawal; Ali Gul Soomro; Shamsuddin Bughio; Rehana Buriro; Aijaz Ali; Saeed Ahmed Soomro (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
The extensive use of antibiotics has developed antibacterial resistance and also may cause toxic effects (hepatotoxicity, nephrotoxicity) on vital organs. To overcome this problem, Scientists gain attention towards medicinal plants. Pure Aloe vera (AV) is a common alternative antimicrobial medicine, hence, the current study was conducted to explore its antibacterial potential and compared it with a commonly used antibiotic amoxicillin. During this study, clinically positive mastitis milk samples (n=50) were collected from buffaloes, after microbial culture analysis. Various concentrations (C1=40, C2=20, C3=10, C4=5, C5=2.5, C6=1.25, C7= 0.62, C8=0.31, C9=0.15, C10=0.07 and C11=0.03µl) of pure AV and amoxicillin (μg/μl) were used to evaluate antibacterial activity through minimum inhibitory concentration (MIC) against Gram-positive organisms including Staphylococcus aureus and Streptococcus agalactiae. The MIC was evaluated based on turbidity and transparency of the medium. Prevalence of S. aureus was recorded at 25 (50 %) whereas, 15 (30 %) positive samples for S. agalactiae and 10 (20 %) positive samples were found in mixed bacterial colonies from milk samples. The mean values of MIC at 10 μl of pure AV showed 50% sensitivity against S. aureus whereas, at 5 μl of pure AV showed 52.5 % sensitivity against S. agalactiae. While amoxicillin inhibited the growth of S. aureus and S. agalactiae at 2.5 μg/μl and 1.25 μg/μl concentrations showed 52.5 %, and 55 % sensitivity respectively. A significant (P ˂ 0.05) difference was noticed between both tested groups. It has been concluded that pure AV possessed antibacterial potential and can be used as a safe and economic alternative against infections caused by S. aureus and S. agalactiae.